Translation Of Indonesian Cultural Terms In Novel Cantik Itu Luka Into Beauty Is A Wound - Lie, Listya Hanatha; Indrawati, Ni Luh Ketut Mas; Setianingsih, Ni Ketut Alit Ida (Denpasar Institute, 2025)
This study examines how cultural terms are translated in Eka Kurniawan’s Cantik Itu Luka and its English translation Beauty Is a Wound (translated by Annie Tucker, 2015). Cultural terms, including references to dukun, wayang, and traditional social practices, pose significant challenges in literary translation due to their deep cultural embeddedness. Drawing on Newmark’s (2008) translation procedures, this study investigates which procedures are applied by the translator to convey cultural meaning while maintaining textual readability. Adopting a qualitative approach, the analysis identifies six translation procedures: transference, transposition, descriptive equivalence, functional equivalence, cultural equivalence, and couplets. The findings indicate that the translator strategically balances cultural preservation and reader accessibility, with transference and cultural equivalence maintaining Indonesian cultural specificity, while descriptive and functional equivalence facilitate comprehension for target readers. This study contributes to literary translation scholarship by demonstrating how systematic procedural choices enable the effective mediation of culturally bound expressions in contemporary Indonesian literature.